Testing Munk's hypothesis for submesoscale eddy generation using observations in the North Atlantic - Buckingham, Christian E.; Khaleel, Zammath; Lazar, Ayah; Martin, Adrian P.; Allen, John T.; Garabato, Alberto C. Naveira; Thompson, Andrew F.; Vic, Clement (Journal of Geophysical Research: Oceans, 2017)
A high-resolution satellite image that reveals a train of coherent, submesoscale (6 km) vortices along the edge of an ocean front is examined in concert with hydrographic measurements in an effort to understand formation mechanisms of the submesoscale eddies. The infrared satellite image consists of ocean surface temperatures at similar to 390 m resolution over the midlatitude North Atlantic (48.69 degrees N, 16.19 degrees W). Concomitant altimetric observations coupled with regular spacing of the eddies suggest the eddies result from mesoscale stirring, filamentation, and subsequent frontal instability. While horizontal shear or barotropic instability (BTI) is one mechanism for generating such eddies (Munk's hypothesis), we conclude from linear theory coupled with the in situ data that mixed layer or submesoscale baroclinic instability (BCI) is a more plausible explanation for the observed submesoscale vortices. Here we assume that the frontal disturbance remains in its linear growth stage and is accurately described by linear dynamics. This result likely has greater applicability to the open ocean, i.e., regions where the gradient Rossby number is reduced relative to its value along coasts and within strong current systems. Given that such waters comprise an appreciable percentage of the ocean surface and that energy and buoyancy fluxes differ under BTI and BCI, this result has wider implications for open-ocean energy/buoyancy budgets and parameterizations within ocean general circulation models. In summary, this work provides rare observational evidence of submesoscale eddy generation by BCI in the open ocean. Plain Language Summary Here, we test Munk's theory for small-scale eddy generation using a unique set of satellite- and ship-based observations. We find that for one particular set of observations in the North Atlantic, the mechanism for eddy generation is not pure horizontal shear, as proposed by Munk et al. (2000) and Munk (2000), but is instead vertical shear, or baroclinic instability. While by ...